2015
DOI: 10.1039/c4em00584h
|View full text |Cite
|
Sign up to set email alerts
|

An isotope hydrochemical approach to understand fluoride release into groundwaters of the Datong Basin, Northern China

Abstract: The hydrogeochemical and isotopic investigations of high fluoride (up to 8.26 mg L(-1)) groundwater in the Datong Basin, Northern China were carried out in order to evaluate the geochemical controls on fluoride enrichment. The groundwater fluoride concentration tends to increase along with the regional groundwater flow path away from the basin margins, towards the central parts of the basin. Groundwater with high F concentrations has a distinctive major ion chemistry, being generally HCO3(-)-rich, Na-rich, Ca-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Su et al (2015) have observed fluoride concentration as high as 8.26 mg/L in groundwater of Datong basin in northern China. In dry regions (characterized by high evaporation rate and low rainfall), high fluoride concentrations in groundwater are due to fluoride dissolved from fluorine-bearing minerals (Zeng 1997).…”
Section: Chinamentioning
confidence: 98%
See 1 more Smart Citation
“…Su et al (2015) have observed fluoride concentration as high as 8.26 mg/L in groundwater of Datong basin in northern China. In dry regions (characterized by high evaporation rate and low rainfall), high fluoride concentrations in groundwater are due to fluoride dissolved from fluorine-bearing minerals (Zeng 1997).…”
Section: Chinamentioning
confidence: 98%
“…Conditions such as semiaridity and high temperature promote effective chemical weathering of fluorinebearing rocks such as granite, gneiss, sandstone and shale (Su et al 2015). Chemical weathering is most effective under arid to semiarid climatic conditions and, thus, may lead to higher fluoride and salinity content.…”
Section: Remark Referencesmentioning
confidence: 99%
“…Groundwater hydrochemistry is very important for understanding the interaction between groundwater and various aquifer minerals and the change of chemical composition (Su et al 2015). The hydro-chemical analysis results of Dali County groundwater sampling points in this study are shown in Table 6.…”
Section: General Chemistry and Uoride Status Of Groundwatermentioning
confidence: 99%
“…Na-HCO 3 type water with low Ca concentration favors the dissolution of fluorite and ion exchange between hydroxide ion and mineral fluorine (Su et al, 2013). Chemical weathering and/or dissolution of fluorine bearing minerals would cause the fluorine release into groundwater (Su et al, 2015). Al/Fe-rich poorly crystalline phases (e.g.…”
Section: Introductionmentioning
confidence: 99%